Semen analysis in a 21 years old man ten years after scrotal lymphedema: a case report - Andrade-Rocha, Fernando Tadeu; Cardona Maya, Walter Dario (Brazilian Journal of Case Reports, 2022)
The semen analysis is the primary test to evaluate the fertile potential of a man, and after a scrotal lymphoedema, it is possible to have some associated reproductive alterations. This case report aims to present the semen analysis of a 21-year-old man ten years after scrotal lymphedema. The man presents azoospermia after suffering from lymphedema at an early age. Based on this case, and as a suggestion, all patients with scrotal lymphedema should be informed of any possible negative effect on the seminal quality and perhaps affectation of their fertility.